Linguistic Culture in Classical Arabic: Aesthetic Perspectives on Ḥadẓ and Ziyādah in the Qur’an - Kojin; Muhammad Dwi Toriyono; Annas Ribab Sibilana; Zaid Ahmad; Ayna Jamila Salsabila (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2025)
This research examines the aesthetics of language culture in the Qur'an through the analysis of language style ḥadẓ (disappearance) and ziyādah (additions) to the rules of grammar that deepen the meaning of holy verses. Ḥadẓ and ziyādah as a linguistic element not only affect the structure of the sentence but also strengthen the meaning, give an aesthetic impression, and invite spiritual reflection of the reader. This study aims to understand how the two language styles enrich the message in the Qur'an. Using qualitative methods and a semiotic approach, this study analyzes the signs and meanings behind the language elements that are displayed or omitted. The results of the survey show that ḥadẓ often used to simplify sentences without reducing meaning, creating a contemplative effect, and focusing attention on the core of the message. On the other hand, ziyādah enriches the text with emphasis and deepening of meaning. This combination of styles forms a distinctive aesthetic dimension, strengthening the message of the Qur'an structurally and meaningfully.